Suicide and gender development an economic exploration of male and female suicide incidence - Almaida, Johanna Denise L.; Panganiban, Jasmine Yari C.
Suicide remains to be one of the primary causes of mortality in the world. Its economic rationality must be understood as the socioeconomic conditions experienced by an individual play an important role in investigating suicide incidence. This research intends to explore the nature of the impact of gender development indicators on suicide rates. The researchers hypothesize that indicators of the human development index (HDI) pertaining to job security are positively associated with suicide rates for both the male and female populations across all development groups, especially in the polar opposite groups (i.e., very high and low human development groups). Meanwhile, per capita income is inferred to be positively related to suicide incidence in the very high HDI group, but the former is negatively related to the latter in the low HDI group. To test this, the age-standardized suicide rates and the data on four HDI indicators (i.e., mean and expected years of schooling, life expectancy, and per capita incomes) and two measures of job insecurity (i.e., unemployment, and vulnerable employment) for the year 2019 were analyzed using two econometric models that utilize log-linear regression. Results show that per capita income was positively related to female suicide rates in the very high HDI group while it was negatively related to the latter in the low HDI group. Male suicide rates were negatively associated with per capita income in both groups. Unemployment and vulnerable employment possess a negative association with female suicide rates in the very high HDI group, while the inverse is true in the low HDI group. In both groups, male suicide rates were negatively associated with unemployment and vulnerable employment. Finally, irrespective of HDI group, males are more prone to suicide than females. These results suggest that societal inequality and engagement in vulnerable jobs are possible explanations behind female suicidal behavior. At the same time, the unconventionality of the patterns of male suicide behavior relative to unemployment and job insecurity necessitates the use of a multifaceted approach in identifying potential causes.